Some friends matter more than others: BMI clustering among adolescents in four European countries. (25th April 2019) - Grund, Thomas U.; Tatum, Travis
Abstract: Previous research stresses the importance of social networks for obesity. We draw on friendship data from 18, 133 adolescents in four European countries to investigate the relationship between individuals' body mass index (BMI) and the BMI of their friends. Our study reveals strong evidence for BMI clustering in England, Germany, the Netherlands, and Sweden; adolescents tend to be friends with others who have a similar BMI. Furthermore, we extend current debate and explore friendship characteristics that moderate the relationship between social networks and BMI. We demonstrate that BMI clustering is more pronounced in (1) strong compared to weak friendships and (2) between adolescents of the same biological sex. These findings indicate thatmore research on social networks and health is needed which distinguishes between different kinds of relationships.